1999
DOI: 10.1007/bf01279257
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of arabinogalactan proteins in pollen grains and tubes as revealed with a monoclonal antibody raised against stylar arabinogalactan proteins

Abstract: Summary. Monoclonal antibody PCBC3, raised against stylar extracts from Nicotiana alata flowers, was deduced from enzymelinked immunosorbent assays and inhibition of immuno-gold labelling on tissue sections to bind specifically to carbohydrate epitopes on arabinogalactan proteins (AGPs) but not to other arabinosecontaining cell wall polysaccharides. When pollen grains of N. tabacum were hydrated in fixative, PCBC3 bound to vesicles in the vicinity of the endoplasmic reticulum but, when grains were hydrated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…The plasma membrane AGP epitope identified by JIM8 has been found in cells of the embryo, the sexual organs of flowers, and pre-lignified xylem vessels, all of which have an altered cell wall composition (Pennell et al 1991). AGPs identified by JIM13 have been detected in the cell walls of growing pollen tubes (Li et al 1992;Ferguson et al 1999) and implicated in the development of root tissue Rae et al 1991) andtracheary elements (McCann 1997;Dolan and Roberts 1995;Schindler 1995). JIM13 labeling in Megaceros secondary walls indicates the presence of AGPs and is consistent with observations in higher plants, particularly in tracheary elements, where it is believed to play a functional role.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The plasma membrane AGP epitope identified by JIM8 has been found in cells of the embryo, the sexual organs of flowers, and pre-lignified xylem vessels, all of which have an altered cell wall composition (Pennell et al 1991). AGPs identified by JIM13 have been detected in the cell walls of growing pollen tubes (Li et al 1992;Ferguson et al 1999) and implicated in the development of root tissue Rae et al 1991) andtracheary elements (McCann 1997;Dolan and Roberts 1995;Schindler 1995). JIM13 labeling in Megaceros secondary walls indicates the presence of AGPs and is consistent with observations in higher plants, particularly in tracheary elements, where it is believed to play a functional role.…”
Section: Discussionmentioning
confidence: 98%
“…CCRC-M7 [which recognizes arabinosylated (1 fi 6)-linked b-galactan] and CCRC-M1 [terminal a-(1 fi 2)-linked fucosyl residue of XG] were a gift from the Complex Carbohydrate Research Center, Athens, Ga, LM5 [which recognizes (1 fi 4)-b-galactan] was purchased from PlantProbes, Leeds, UK, and anti-(1 fi 3)-b-glucan antibody was purchased from Biosupplies, Australia. Immunogold labeling was performed as described by Ferguson et al (1998Ferguson et al ( , 1999. Primary antibodies omitted from the labeling procedure acted as a control.…”
Section: Immunogold Labeling and Transmission Electron Microscopymentioning
confidence: 99%
“…Very recently several AGP epitopes have been found in vesicles located in the vicinity of ER (Ferguson et al 1999) or in Golgi apparatus (Vicr6 et al 1998, Winicur et al 1998) of some dicotyledonous species. Ferguson et al (1999) used monoclonal antibody PCBC3 which recognizes both arabinosyl and galactosyl residues in relatively large (0.4 gm) electron-lucent vesicles near the ER of tobacco cells. Vicr6 et al (1998) have reported that antibody Gal4 against ~-(1---~6)-D-galactan labels trans-type cisternae and vesicles of Golgi apparatus within flax meristematic root cells.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of in vitro-cultured pollen tubes of tobacco, petunia and lily suggest that at least part of the primary wall is lost during growth (Derksen et al 1995b(Derksen et al , 1999b. Deposition of the probably more persistent, cellulosic part of the primary wall occurs at the tip and continues into the tube, where the secondary wall is formed (Derksen et al 1995a(Derksen et al ,b, 1999bFerguson et al 1999). Cellulose of both the primary and secondary walls and callose of the secondary wall are supposedly deposited by synthases in the plasmamembrane that originally must have been delivered in the tip by the SV.…”
Section: The Pollen Tube Wallmentioning
confidence: 99%